Discovery of Benzotriazolo[4,3-d][1,4]diazepines as Orally Active Inhibitors of BET Bromodomains - Taylor, Alexander M. (ACS Med Chem Lett, 2015)
[Image: see text] Inhibition of the bromodomains of the BET family, of which BRD4 is a member, has been shown to decrease myc and interleukin (IL) 6 in vivo, markers that are of therapeutic relevance to cancer and inflammatory disease, respectively. Herein we report substituted benzo[b]isoxazolo[4,5-d]azepines and benzotriazolo[4,3-d][1,4]diazepines as fragment-derived novel inhibitors of the bromodomain of BRD4. Compounds from these series were potent and selective in cells, and subsequent optimization of microsomal stability yielded representatives that demonstrated dose- and time-dependent reduction of plasma IL-6 in mice.